The Knowledge of Romani and School Readiness of Roma Children - Kyuchukov, Hristo; Samko, Milan; Kopcanova, Dagmar; Igov, Peter (Lesya Ukrainka Eastern European National University, 2016)
The paper presents results from an international research project looking at Roma children between the ages of 3 and 6 years old. Thirty Roma children from Southwest Bulgaria and 30 Roma children from East Slovakia were tested with a psycholinguistic test in Romani language, measuring the knowledge of different grammatical categories. In most East European countries, the children are tested employing psychological/IQ tests in the official languages of the country and if the child does not understand the test task, because of a lack of knowledge in that language, s/he is deemed to have “light mental retardation”. The knowledge of the children on different grammatical categories in their mother tongue is not taken into account. For the first time in Europe, a psycholinguistic test was developed for measuring the knowledge in Romani (comprehension and production). Categories such as wh-questions, wh-complements, passive verbs, possessiveness, tense and aspect, learning new nouns and verbs are measured with newly developed test. The knowledge of the children is connected with two theories: the ecological theory of Ogbu (1978) and the integrative theory of child development (García Coll et al. 1996). Ogbu’s theory stresses the importance of the home culture in the development of the children and the theory of García Coll and her collaborators presents the home environment and the SES of the families as an important predictor for language development and school readiness of the minority/migrant children. У статті представлено результати міжнародного дослідницького проекту, в якому взяли участь діти ромів віком від 3 до 6 років. Тридцять дітей із сімей ромів з Південно-західної Болгарії та тридцять дітей із сімей ромів зі Східної Словаччини пройшли психолінгвістичний тест ромською мовою з метою оцінки знань різних граматичних категорій. Автори зазначають, що в більшості країнах Східної Європи діти проходять психологічні тести і/або тести на визначення рівня інтелекту на офіційних мовах країни і, якщо дитина не розуміє тестове завдання через відсутність знань на цій мові, вважають, що їй характерна «легка форма розумової відсталості». Відтак, знання різних граматичних категорій дітьми їхньою рідною мовою не прийнято брати до уваги. Уперше в Європі розроблено психолінгвістичний тест ромською мовою для оцінки знань (розуміння та породження). Розроблений тест спрямований на оцінку знань таких категорій, як Wh-запитання, Wh-доповнення, пасивні дієслова, присвійність. Рівень розвитку дітей автори повʼязують із двома теоріями: екологічною теорією Огбу (1978) та інтегративною теорією розвитку дитини (García Coll et al. 1996). Теорія Огбу підкреслює важливість рідної культури в розвитку дітей і є суголосна з теорією Гарсії Кол і колег, адже полягає в тому, що ключовими чинниками розвитку мови та рівня підготовленості дітей до школи є домашнє оточення та соціально-економічний стан сімей, у яких виховуються діти-мігранти чи діти з числа меншин.
Keywords: Roma children; ecological theory; integrative theory; Romani language assessment test; school readiness; ромські діти; діти ромів; екологічна теорія; інтегративна теорія; тест на оцінку знань ромської мови; підготовленість до школи